Enhancing the ROS generation ability of a rhodamine-decorated iridium(iii) complex by ligand regulation for endoplasmic reticulum-targeted photodynamic therapy. Issue 44 (22nd October 2020) - Zhou, Lihua; Wei, Fangfang; Xiang, Jingjing; Li, Hongfeng; Li, Chunbin; Zhang, Pengfei; Liu, Chuangjun; Gong, Ping; Cai, Lintao; Wong, Keith Man-Chung
Abstract : A design strategy for boosting the ROS generation of rhodamine-decorated cyclometallated iridium(iii ) complexes by ligand regulation for endoplasmic reticulum-targeted precise photodynamic therapy. Abstract : The endoplasmic reticulum (ER) is a very important organelle responsible for crucial biosynthetic, sensing, and signalling functions in eukaryotic cells. In this work, we established a strategy of ligand regulation to enhance the singlet oxygen generation capacity and subcellular organelle localization ability of a rhodamine-decorated iridium(iii ) complex by variation of the cyclometallating ligand. The resulting metal complex showed outstanding reactive oxygen species generation efficiency (1.6-fold higher than that of rose bengal in CH3 CN) and highly specific ER localization ability, which demonstrated the promise of the metal-based photo-theranostic agent by simultaneously tuning the photochemical/physical and biological properties. Additionally, low dark cytotoxicity, high photostability and selective tumour cell uptake were featured by this complex to demonstrate it as a promising candidate in photodynamic therapy (PDT) applications. In vivo near infrared fluorescence (NIRF) imaging and tumour PDT were investigated and showed preferential accumulation at the tumour site and remarkable tumour growth suppression, respectively.